First Mile Challenges to Last Mile Rhetoric: Exploring the Discourse between Remote and Rural First Nations and the Telecom Industry - Philpot, Duncan; Beaton, Brian; Whiteduck, Tim (The Journal of Community Informatics, 2013)
Solving Canada’s digital divide remains a significant issue, particularly considering how broadband networks have an impact on remote and rural areas politically, economically, socially, and culturally. Attached to this, as well, are the politics of the historical relationship between remote and rural First Nation communities, corporations, and the government. The way in which the relationship between remote and rural First Nations, the federal and provincial governments, and the telecommunications industries is reproduced is largely through discursive means. One of the consequences of this is that many outsiders to this issue are largely misinformed through documents and press releases. These documents frame remote and rural First Nations as helpless and dependent upon government and telecom industry intervention in order to secure their dependence upon their services. We argue that this is another form of political colonialism; a form of colonialism which seeks to create dependence upon the service economy for its own survival. In this paper, we examine the discourse surrounding the issue of remote and rural broadband connectivity as a means of exploring the reproduction of established narratives of First Nations dependence upon aid and service. We also explore how First Nations communities are using websites and documents of their own to counter these portrayals of their ‘plight’ by emphasising their desire to own and operate ICT services in their communities with local members, for local members. We conclude that there is a significant challenge that remote and rural First Nations face, but that the steps that have been taken are towards escaping the cycle of co-dependency.